Fatigue Behavior of an Al-12.7Si-0.7Mg Alloy Processed by Extrusion and Heat Treatment - Liu, Fang; Yu, Fuxiao; Zhao, Dazhi; Gao, Li (Frontiers in Materials, 2021)
The fatigue life of hot extruded Al-12.7Si-0.7Mg alloy under T1, T4 and T6 conditions was studied. The microstructure and tensile properties of the alloy were investigated in order to analyze the fatigue behavior. The results of fatigue test show that extruded Al-12.7Si-0.7Mg alloy provides greater fatigue life compared to cast Al-Si alloy, which explained by the refined microstructure characterized by fine Si particles uniformly distributed in the Al matrix of fine equiaxed grains promoted by hot extrusion. The fatigue property of the alloy in T6 treatment is higher than that in T4 and T1 conditions due to the precipitation strengthening.